The Rise and Fall of Consumption in the 2000s: A Tangled Tale. (14th May 2018) - Demyanyk, Yuliya; Hryshko, Dmytro; Luengo‐Prado, María José; Sørensen, Bent E.
Abstract : US consumption has gone through steep ups and downs since 2000. We quantify the statistical impact of income, unemployment, house prices, credit scores, debt, financial assets, expectations, foreclosures and inequality on county‐level consumption growth for four subperiods: the 'dot‐com recession' (2001–3), the 'subprime boom' (2004–6), the Great Recession (2007–9) and the 'tepid recovery' (2010–12). Consumption growth cannot be explained by a few factors; rather, it depends on a large number of variables whose explanatory power varies by subperiod. Growth of income, growth of housing wealth and fluctuations in unemployment are the most important determinants of consumption, significantly so in all subperiods, while fluctuations in financial assets and expectations are important during only some subperiods. Lagged variables, such as the share of subprime borrowers, are significant but less important.